TINGKAT PENGETAHUAN GENERASI Z TENTANG PENGGUNAAN SKINCARE YANG AMAN DI RW 08 KELURAHAN PATRANG KABUPATEN JEMBER - Denok Risky Ayu Paramita; Dinda Cania Safira Jayanti; Dyan Maulani; Kukuh Judy Handojo (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2022)
The purpose of this study was to determine the level of knowledge of Generation Z about the safe use of skincare in RW 08 Patrang Village, Jember Regency. The research method used a descriptive method with a cross-sectional analysis design. The sampling technique was total sampling with 92 respondents. The research was conducted using a questionnaire. The results showed that the level of knowledge of respondents in the realm of knowing was 86,6%; in the realm of understanding 91,0%; and in the realm of application 91,3%. From the results of these percentages, it can be concluded that the level of knowledge of generation Z about the safe use of skincare in RW 08 Patrang Village, Jember Regency is in a good category.